2022
DOI: 10.1371/journal.pone.0279465
|View full text |Cite
|
Sign up to set email alerts
|

Availability, price, and affordability of medicines used for the management of Covid-19 in health facilities of Dessie town WHO/HAI survey

Abstract: Background The rapidly spreading nature of Covid-19 virus associated with its high mortality and mortality rate is triggering an unprecedented public health crisis. The study assessed the availability, price, and affordability of medicines used in the management of Covid-19 in health facilities of Dessie town. Methods A retrospective cross-sectional study design was employed in the health facilities of Dessie town from September 1 to September 20, 2021. Data was collected using a standard checklist adopted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A study by (Lee Ventola, 2011) found that medication errors and drug shortages in the United States were associated with increased healthcare costs. A study by (Mohammed et al, 2022) found that drug shortages in Ethiopia were associated with increased healthcare costs, with each day of drug shortage resulting 33.33% and 28.57% higher prices than international prices in private and public health facilities, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by (Lee Ventola, 2011) found that medication errors and drug shortages in the United States were associated with increased healthcare costs. A study by (Mohammed et al, 2022) found that drug shortages in Ethiopia were associated with increased healthcare costs, with each day of drug shortage resulting 33.33% and 28.57% higher prices than international prices in private and public health facilities, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%